2017
DOI: 10.1159/000481612
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Adiponectin Against Diabetic Renal Injury in a Mouse Model of Diabetes

Abstract: Abstract:Background/Aims: Adiponectin (Apn) has shown anti-diabetic and anti-inflammatory potential. In the study, we studied and tested the protective effects of Apn against diabetic renal injury and the possible mechanism of these effects. Methods: After 1 week of adaptive feeding, 30 mice were randomly divided into 5 groups: the control group, the model group, the Apn (L) group, the Apn (M) group and the Apn (H) group. All mice were marked and weighed. Following 4 weeks of a pro-diabetic high-fat diet, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In our study, END was able to prevent the expected hyperglycemia and hyperinsulinemia after HFD. In this context, Hu et al (2017) in high-fat fed and streptozotocin-induced diabetic mice found that different concentrations of intravenous-delivered adiponectin (10, 25, and 100 mg/kg) protected the animals against hyperglycemia, which may be one of the reason why END was also able to partially protect the animals against hyperinsulinemia. However, no clear mechanisms were explained.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, END was able to prevent the expected hyperglycemia and hyperinsulinemia after HFD. In this context, Hu et al (2017) in high-fat fed and streptozotocin-induced diabetic mice found that different concentrations of intravenous-delivered adiponectin (10, 25, and 100 mg/kg) protected the animals against hyperglycemia, which may be one of the reason why END was also able to partially protect the animals against hyperinsulinemia. However, no clear mechanisms were explained.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies based on in vivo experiments have confirmed the renoprotective effect of APN. In vivo experiments performed by Fang F et al confirm that APN-treated mesangial cells can inhibit high glucoseinduced ROS production and activation of nicotinamide adenine dinucleotide phosphate oxidase in mice with diabetic nephropathy [36].…”
Section: Role Of Adiponectin In Reducing Renal Inherent Cell Damagementioning
confidence: 93%